The unit size effect on chocolate consumption: How to make consumers eat less? (The unit size effect on chocolate consumption) - Enikő Kontor; Mihály Soós; Nikolett Balsa-Budai; Sándor Kovács; Zoltán Szakály (Heliyon)
Understanding the impact of environmental stimuli, such as nudges, on consumption behavior is crucial for developing effective dietary interventions. This study investigates the unit size effect, a behaviourally-oriented nudge, on chocolate consumption. In particular, it examines how different unit sizes and the presence or absence of packaging influence the quantity of chocolate consumed and the perceived energy intake in grams and calories. The research contributes to the theoretical framework of nudge theory, particularly the concept of unit bias, which suggests that larger units lead to higher consumption volumes. The novelty of this paper lies in its exploration of the combined effects of unit size and packaging and healthy lifestyle on consumption behavior, a relatively under-researched area. The methodology involved an experiment with four focus groups, differentiated by health-consciousness, who were provided with chocolate in varying unit sizes and packaging conditions. The data from the experiments were subjected to a three-way repeated measures ANOVA (RM-ANOVA) model. The results indicated that larger unit sizes significantly increase consumption compared to smaller units, regardless of packaging. This demonstrates that unit size has a greater impact on consumption than packaging, reinforcing the power of unit bias. The health-conscious participants consumed a markedly lower quantity of packed chocolates and exhibited a tendency to significantly overestimate the amount consumed, suggesting that those who are health-conscious may be more conscious of their diet. The findings support the effectiveness of behaviourally-oriented nudge marketing tools in influencing consumption behavior without altering consumer knowledge or emotions.